Digital Governance, DDDM, and SIKD: Drivers of Local Government Performance - Istiyani Ratna Dewi; Sari, Dien Noviany Rahmatika; Sari, Abdulloh Mubarok (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of digital governance capability, data-driven decision-making (DDDM), and the utilization of the Regional Financial Information System (SIKD) on the performance of Regional Apparatus Organizations (OPD), with transparency in regional financial management as an intervening variable. Data from 150 respondents across all OPDs in Brebes Regency were analyzed using PLS-SEM. DDDM and SIKD utilization positively and significantly affect transparency and OPD performance, while digital governance capability does not. Transparency positively affects performance and mediates the effects of DDDM and SIKD utilization, but not of digital governance capability, supporting evidence-based bureaucratic reform. Keywords: Digital Governance Capability; Data-Driven Decision Making; Regional Financial Information System (SIKD); Regional Financial Management Transparency; Local Government Performance